Cardiac amyloidosis in the practice of a cardiologist and therapist. Case report - T. V. Nikiforova; Z. М. Magomedova; M. F. Magaramova; E. S. Pershina; D. Yu. Shchekochikhin; D. A. Andreev (Consilium Medicum)
Amyloidosis is a heterogeneous group of diseases associated with abnormal protein aggregation and deposition in organs and tissues as insoluble fibrils. The heterogeneity of the clinical manifestations of these disorders is due to various precursor proteins and damage to various organs and systems. Diagnosis of the disease is complex and requires high clinical alertness from physicians. Unfortunately, in most cases, the patient's diagnostic path is unreasonably long, and the effectiveness of therapy is primarily determined by the timing of diagnosis. Often, the cardiologist is the first specialist to be approached by a patient with this severe disease. The article highlights approaches to early diagnosis of amyloidosis with heart involvement.